La influencia del pensamiento de Simón Bolívar sobre la educación y la creación de la Universidad Central de Quito y la Escuela de Medicina en el año 1.826 - López Pulles, Ramiro (2018)
Context: Bolivar's thought on education was decisive in the creation of new universities born after the independence of America. Bolivar drove the Lancasterian method.Discussion: in response to medical paternalism, four basic principles have been proposed concerning the position of themutual teaching was practiced by some private teachers and in the free schools of some convents. The Lancasterian company was the one that won the support of government and the public, and encouraged the establishment of mutual teaching schools nationwide. The Lancasterian system was of great importance due to its characteristics, since as there were not a large number of teachers, children with outstanding abilities were trained and oriented to teach the rest of the group and these reduced costs and improved access to education.Conclusion: the reforms that took place in 1827, based on the ideas of Bolívar that promulgated the lancasterian method, in the field of medical education in Quito were vital, since even a medical faculty of its own was created at the Central University of Quito. This was thanks to the management of José Miguel Carrión and Valdivieso, rector of the university, whose legacy is of great importance for the functioning and existence of the current Faculty of Medical Sciences.